Comparative Analysis of Quinolone Resistance in Clinical Isolates of Klebsiella pneumoniae and Escherichia coli from Chinese Children and Adults. (10th February 2015) - Huang, Ying; Ogutu, James O.; Gu, Jiarui; Ding, Fengshu; You, Yuhong; Huo, Yan; Zhao, Hong; Li, Wenjing; Zhang, Zhiwei; Zhang, Wenli; Chen, Xiaobei; Fu, Yingmei; et al.
Abstract : The objective of this study was to compare quinolone resistance and gyrA mutations in clinical isolates of Klebsiella pneumoniae and Escherichia coli from Chinese adults who used quinolone in the preceding month and children without any known history of quinolone administration. The antimicrobial susceptibilities of 61 isolates from children and 79 isolates from adults were determined. The mutations in the quinolone resistance-determining regions in gyrA gene were detected by PCR and DNA sequencing. Fluoroquinolone resistance and types of gyrA mutations in isolates from children and adults were compared and statistically analyzed. No significant differences were detected in the resistance rates of ciprofloxacin and levofloxacin between children and adults among isolates of the two species (all P > 0.05 ). The double mutation Ser83→ Leu + Asp87→ Asn in the ciprofloxacin-resistant isolates occurred in 73.7% isolates from the children and 67.9% from the adults, respectively (P = 0.5444 ). Children with no known history of quinolone administration were found to carry fluoroquinolone-resistant Enterobacteriaceae isolates. The occurrence of ciprofloxacin resistance and the major types of gyrA mutations in the isolates from the children were similar to those from adults. The results indicate that precautions should be taken on environmental issues resulting from widespread transmission of quinolone resistance.